Restorative justice in Indonesia corruption crime: a utopia - Andini, Orin Gusta; Nilasari, Nilasari; Eurian, Andreas Avelino (Legality : Jurnal Ilmiah Hukum, 2023)
The discourse about combating corruption through restorative justice has produced positive and negative outcomes. The extraordinary crime of corruption features several distinguishing characteristics distinct from those of general crimes. Even though restorative justice is a method of modernizing the way law enforcement is practiced, the policy that is used to put it into effect needs to be extremely selective and cautious. This study will investigate the applicability of restorative justice to acts of corruption. The research comprises two research questions. 1) How is the concept of Restorative Justice regulated in Indonesia? 2) How is the analysis of Law Number 20 of 2001 concerning Amendments to Law Number 31 of 1999 concerning the Eradication of Corruption Crimes on the resolution of corruption through restorative justice? The research employed a normative method that combined a statutory and conceptual approach to problem formulation, indicating that, first, the restorative justice concept is regulated in Indonesia through technical regulations developed by each law enforcement agency, with limited implementation. Second, restorative justice in the settlement of corruption contravenes Article 4 Law Number 20 of 2001 concerning Amendments to Law Number 31 of 1999 concerning the Eradication of Corruption Crimes and is a step back in efforts to eradicate corruption, as well as inconsistent with the state's obligation to support policies and effective practices in eradicating corruption as regulated by UNCAC.